Simulation Of Cantilevered Piezoelectric Energy Harvesters - Mohamed Ghouse, Muhammad Suffi Fazari (Universiti Sains Malaysia, 2022)
Vibration-based energy harvesting had been extensively investigated by several researchers over the last decade. The use of piezoelectricity is known for its mechanical vibration-to-electricity conversion. The piezoelectric energy harvesters (PEHs) efficiency is dependent on the cantilever geomtry and the vibration source frequency. In this paper, cantilevered beams with piezoelectric layers of PZT-5A material are employed as piezoelectric energy harvesters. Three kinds of PEH cantilever beams were constructed which are the unimorph, bimorph and bimorph without load. The simulation of these three beams were made on ANSYS software. This was meant for the study of the performance for each of the PEH cantilever beams and they had proven distinctions among them. Modal analysis and Harmonic Response analysis were setup and run for the three types of beams and the results were validated. The outcome of the simulation analysis was generated and interpreted graphically which shows the model deformation, voltage and the frequency response for all the beams with same weight of load and dimensions.